Slurry aluminizing of IN‐800HT austenitic stainless steel and pure nickel. Correlations between experimental results and modelling of diffusion. Issue 10 (16th February 2016) - Pedraza, F.; Proy, M.; Boulesteix, C.; Krukovskyi, P.; Metel, M.
Abstract : Slurry aluminide coatings were elaborated on IN‐800HT and pure Ni. After spray of the slurry, the annealing treatment was performed in Ar(g) at 400 °C for 3 h, then by 650 °C for up to 5 h. This brought about major Al diffusion into the substrate following parabolic kinetics. After 5 h at 650 °C, stabilization of the B2–(Fe, Ni)Al and β‐NiAl coatings in, respectively, the IN‐800HT and pure Ni substrates was achieved at 1100 °C for 1 h. The coatings were then exposed to air, argon and steam for 2000 h at 650 °C. The Al diffusion profiles were acquired by EDS analyses and were equivalent in Ar(g) and steam whereas significant consumption of Al occurred in the external coatings exposed to air. Five hundred hours annealing steps were thus carried out in Ar(g) to gather the Al composition profiles with exposure time till 2000 h to model diffusion and to estimate lifetime. These were performed using a numerical model and the so‐called inverse problem solution, which appeared to be unsuccessful due to the insufficient quality of experimental data expressed through a quantitative criterion ("informativity"). Some recommendations are proposed to increase the accuracy of the assessment of the model parameters. Abstract : Aluminium slurry coatings were successfully deposited on IN‐800HT. The Al diffusion profiles were modelled and fitted with the experimental ones obtained at 650 °C up to 2000 h.